Bibliometric Analysis of Heterarchy: Toward a Paradigm Shift in Public Administration Studies - Kudus, Imanudin; Nurasa, Heru; Widianingsih, Ida; Karlina, Nina; Jawan, Jayum Anak (Jurnal Manajemen Pelayanan Publik, 2024)
The study of public administration developed from the Old Public Administration to the New Public Service, bringing management and public organizations to shift from the traditional paradigm to the modern paradigm. Organizations were originally seen as machines that emphasized hierarchy. The modern perspective states that hierarchy is no longer an effective organizational strategy. The new public administration steered organizations toward collaboration, consensus, and democratic management to encourage the development of a heterarchical approach. The research results were visualized using bibliographic research methodology and the VOSviewer program. Access Scopus database data using the following keywords, title-abs-key (" heterarchy ") and ((pubstage (pubstage ") and (limit-to (doctype, "ar") and (limit-to (language, "English") and (limittoes (srctype, "j"). The research results provide an overview of the quality and quantity of articles about heterarchy around the world. Global trends indicate high interest in this research topic. In addition, the works that have been published are of good quality, marked by a high number of citations. To find novelty, the author tries to take topics that are still rarely researched. Apart from that, to get a big chance of publication, the author considers several aspects, such as country, affiliation, influential journals.